A survey on recycling attitudes of engineering students at UiTM Shah Alam: article - Mohamad, Nur Natasha; A. Kadir, Sharifah Aishah (2016)
The generation of municipal solid waste (MSW) in Malaysia over the past 10 years has increased by 95 percent due to rapid development in the urban areas. 16.76 million tonne of waste is expected to be generated by Malaysian in the year 2020. 40 percent reduction of waste disposed to landfill by year 2020, through recycling and intermediate treatment such as waste to energy, composting and material recovery. Presently, there are about 70 percent of waste produced reported to be collected and 95 percent of it are disposed in landfills with only 5 percent left are being recycled. It clearly shows the awareness in reducing waste through recycling is still at infant among Malaysians. Hence, a proper solid waste management should be enhanced through education among youngsters to ensure an integrated solid waste management. The purpose of the study research is to determine the awareness of engineering students at UiTM on recycling practices through survey and study on the effectiveness of recycling bins at the engineering students’ centre. Questionnaires are being distributed among students where the responses are received directly. The data collected are analyzed using statistical analysis. Results shows that there is significant relationship (p<0.05) between gender and knowledge on recycling using Chi square test and gives an insignificant relationship (p>0.05) between knowledge and awareness of students towards recycling using partial correlation